Současné možnosti operačního řešení krční spondylogenní myelopatie - Ryba, Luděk; Chaloupka, Richard; Matejička, Dušan (Neurologie pro praxi, 2023)
The principle of the surgical treatment of cervical spondylotic myelopathy is to eliminate the compression of nerve structures or increase the diameter of the spinal canal. Surgery options are divided into anterior, posterior, and combined approaches. Through the anterior approach, the intervertebral discs are removed, and if necessary also vertebral body. In addition to the previously used bone graft, mostly an autologous graft from the pelvis, there has been significant progress in the possibility of using various materials, metal, titanium, PEEK, Trabecular Metal, filled with artificial bone with the aim of rapid growth into neighboring vertebral bodies. There is also great development in the use of front plates, currently already 3rd generation, with angle-adjustable and lockable screws in the plates. For the posterior approach, laminectomy and laminoplasty are used, with the possibility of fixing the laminae with special plates. In an effort to save muscle attachments, there is the possibility of unilateral laminoplasty.
Keywords: pooperační komplikace; Decompression, Surgical; Internal Fixators; Humans; Laminoplasty; lidé; krční obratle; laminoplastika; Spinal Stenosis; chirurgická dekomprese; laminektomie; Postoperative Complications; nemoci míchy; Laminectomy; Spinal Cord Diseases; interní fixátory; Cervical Vertebrae; Diagnostic Imaging; diagnostické zobrazování; diskektomie; spinální stenóza; Diskectomy